Round & Round…A Peak into the World of a Restless Child Demystifying ADHD - Pandit, Parimal (Voices of Teachers and Teacher Educators, 2019)
This paper attempts to understand the probable reasons for these conditions and how as the ad-ult community of teachers, parents, counsellors and doctors can support the health of such children. One thing is clear - children are not the cause of their health deficits. The community needs to take the onus for this and look at the modifications needed to the child’s environment, in his education, diet, exposure and most importantly in his interactions. A focus on these parameters will have a defining impact on the incidence of ‘ADHD- Attention Deficit Hyperactivity Disorder’.